PENGARUH BRAND AMBASSADOR RED VELVET DALAM IKLAN “MY BEAUTY MY RULE” TERHADAP BRAND IMAGE AZARINE COSMETIC (Survei Pada Followers Instagram @azarinecosmeticofficial) - Sagita, Selvi; Sari, Wina Puspita; Fatimah, Anggun Nadia (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2024)
Advertising is an effective and efficient marketing strategy. Companies often use public figures or celebrities as brand ambassadors to make their advertisements more engaging. The existence of brand ambassadors also contributes to a strong public perception of the brand. The aims of this research is to determine the influence of Red Velvet as brand ambassadors in in the